Research on the Application of Qufu Cultural and Creative Products Under Design Psychology - Sun, Xun; Li, Xiyun; Ren, Weijia (Transactions on Economics, Business and Management Research, 2024)
Based on design psychology theory, this research explores the connection between design psychology and cultural and creative products by considering consumer motivation and the relationship between design and demand. It integrates social, consumer, and design psychology into the design concept of cultural and creative products, aiming to enhance the cultural connotation and user psychological needs of Qufu cultural and creative products, thereby promoting the continuous development of Qufu’s cultural and creative industry.